Assessing the Environmental Adaptation of Wildlife and Production Animals Applications of Physiological Indices and Welfare Assessment Tools - Narayan, Edward (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Wild animals under human care as well as domesticated farm production animals are often exposed to environmental changes (e.g., capture and transportation). Short-term or acute changes in physiological indices (e.g., heart rate, respiration, body temperatures, immune cells, and stress hormonal biomarkers) provide crucial information regarding the responses of animals to novel environments, and they could provide crucial determining factors for the long-term health and welfare of animals. This Special Issue includes experimental research papers that demonstrate the applications of physiological indices and welfare assessment methods (e.g., morphological and morphometric data, behavioural assessments, thermal profiles, and physiological markers) in any wildlife or production animal (e.g., rescued and rehabilitating animals, pets, competition animals, farm animals, and zoo animals), in response to environmental and management related factors. The goal is to provide examples of new research and techniques that can be used to monitor short- and long-term environmental adaptation of animals under human care.